NEW APPROACH FOR BRAIN TUMOR STAGE DETECTION AND AREA CALCULATION - Sandhya Manohar Karande; Swapnali Vijay Kulkarni; Prof. M. C. Kshirsahar (International Journal of Innovations in Engineering Research and Technology, 2021)
A tumor also known as neoplasm is a growth in the abnormal tissue which can be differentiated from the surrounding tissue by its structure. A tumor may lead to cancer, which is a major leading cause of death. Cancer incidence rate is growing at an alarming rate in the world. Great knowledge and experience on radiology are required for accurate tumor detection in medical imaging. Automation of tumor detection is required because there might be a shortage of skilled radiologists at a time of great need. We propose a new approach for brain tumor detection that can detect and localize brain tumor in magnetic resonance imaging. The proposed brain tumor detection and area calculation framework comprises image acquisition, pre-processing, segmentation, extraction, classification and area calculation and stage detection.